STRATEGI EKONOMI POLITIK SAMSUNG GROUP COMPANY DALAM MENGUASAI PASAR SELULER SMARTPHONE DI INDONESIA - Try Suzana Purba; Afrizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research explain about South Korea Multinational Corporationbusiness in Indonesia, Samsung Group Company. At this time Samsung Companyhas become the leader and risen to be number one market smartphone inIndonesia. Samsung’s smartphone could defeat product of Apple Inc, Research inMotion (RIM) Coorperation, and the other phone’s Companies. This research wasconducted using library research methods where the data and information areobtained from sources that are relevant to this problem of the research. Thisresearch uses qualitative analysis and to analyze the strategy of Samsung GroupCompany is used competitive adventage theory by Michael E. Porter. SamsungGroup Company realize that to make competitive manufacture is used buildresearch and development (R&D) overseas and that forced by inovativemanagement. The writer used data which was collected from journals, books, andwebsite to analyze the research. This research finds out that the strategy ofSamsung Group Company in Indonesia was using Inovative product for customerin Indonesia, There are quality inovative, design inovative, and creativemanagement so Samsung products can be the favorite product in Indonesian.Key words: Samsung smartphone, competitive manufacture, inovativemanagement samsung